Pengaruh Spiritual Leadership Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada CV. Maju Djaya Beton - Ananda Lutfiyatul Hasanah; Nurhidayah Nurhidayah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the influence of spiritual leadership and job satisfaction on employee performance CV. Forward Djaya Concrete. The location of this research was conducted on employees who work at CV. Forward Djaya Concrete. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to employees of CV. Maju Djaya Beton selected by purposive sampling. Determination of the number of samples using the Maholtra formula and the results obtained were 95 respondents. Data were analyzed using multiple linear regression test and determination test. Based on the results of data analysis, the results of the F test indicate that spiritual leadership and job satisfaction simultaneously have a significant and positive effect on employee performance at CV. Forward Djaya Concrete. Furthermore, the results of the t test show that spiritual leadership and job satisfaction partially have a significant and positive effect on employee performance at CV Maju Djaya Beton. The results of the determination test show that the percentage is 31.6%, where employee performance is able to be influenced by spiritual leadership and job satisfaction. It is better if a leader in deciding the appropriate decision must be considered again and discussed more thoroughly, in order to provide useful solutions for the progress of the company. Keywords: Employee Performance, Spiritual Leadership, Job Satisfaction